Design and Development of Raw Material Management Information Systems for Pelangi Cake Bakery - Christian, Vincent Dennis; Widjaja, Prya Artha (PT FORMOSA CENDEKIA GLOBAL, 2024)
Effective management of raw materials is an important factor in maintaining business operations, especially for manufacturers. Pelangi Cake Bakery face some challenges in managing its raw materials. The challenges it faces are in terms of documentation and maintaining the supply of its raw materials. This research aims to build a raw material management information system that could help Pelangi Cake Bakery to effectively and efficiently manage its raw materials inventory. The system would be able to provide accurate and real-time information, as well as a centralized documentation that could help its users to make decisions. The findings of this research are that the main problem Pelangi Cake Bakery had was there were no documentation done in its inventory management. Therefore, the system is designed to be focused on the documentation of the usage of raw materials, stock reports, and to encourage collaboration between people in the raw material management activity